2019
DOI: 10.3390/app9224823
|View full text |Cite
|
Sign up to set email alerts
|

A Flutter-Based Electromagnetic Wind Energy Harvester: Theory and Experiments

Abstract: Wind energy harvesting is a promising way to offer power supply to low-power electronic devices. Miniature wind-induced vibration energy harvesters, which are currently being focused on by researchers in the field, offer the advantages of small volume and simple structure. In this article, an analytical model was proposed for the kinetic analysis of a flutter-based electromagnetic wind energy harvester. As a result, the critical wind speeds of energy harvesters with different magnet positions were predicted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…They found that, when the two‐flag harvesters were separated by a pair of distances, the wind speed and pressure difference promoted contact between the two harvesters, showing superior output performance than a single flag‐type FEH. Perez et al 65,66 used the flutter characteristics of the flexible film to achieve energy harvesting by placing the flexible film between two parallel electrodes, as shown in Figure 9C, reaching 481 μW and 2.1 mW at wind speeds of 15 and 30 m/s, respectively.…”
Section: Principle and Structural Designmentioning
confidence: 99%
“…They found that, when the two‐flag harvesters were separated by a pair of distances, the wind speed and pressure difference promoted contact between the two harvesters, showing superior output performance than a single flag‐type FEH. Perez et al 65,66 used the flutter characteristics of the flexible film to achieve energy harvesting by placing the flexible film between two parallel electrodes, as shown in Figure 9C, reaching 481 μW and 2.1 mW at wind speeds of 15 and 30 m/s, respectively.…”
Section: Principle and Structural Designmentioning
confidence: 99%
“…Traditional large megawatt-class wind turbines are large, costly, and complex, limiting their scope of application [7]. Many works have been done in the field of small wind energy harvesters for this purpose by researchers using operational mechanisms of piezoelectric [8,9], electromagnetic [10,11], electrostatic [12,13], triboelectric [14,15], and hybrid methods [16,17]. Among them, the piezoelectric-based wind energy harvester has many advantages such as low cost, simple structure, easy miniaturization, high energy density, no electromagnetic interference, and not required to be activated by an external voltage source [18].…”
Section: Introductionmentioning
confidence: 99%
“…While resonance and vortex induced vibrations experience significant oscillations within a limited range of wind speeds, flutter on the other hand can occur over a larger range of wind speeds due to its self-sustained behavior [6], making it a promising choice for energy harvesting. Several designs have previously been proposed to harvest wind energy from flutter oscillations using membranes [7], cantilever beams [8] or flags [9] but the one that stands out is the dual cantilever flutter (DCF) design by Hobeck et al [10,11] due to its unique characteristics. The DCF design consist of two vertical cantilever beams that are placed side by side separated by a small gap and facing the direction of the wind flow.…”
Section: Introductionmentioning
confidence: 99%